Hybrid Look-Up-Tables Based Behavioral Model for Dynamic Nonlinear Power Amplifiers - Ahmad I. Dalbah; Oualid Hammi; Azzedine Zerguine (IEEE Access, 2020)
A new look-up table based behavioral model for dynamic nonlinear power amplifiers is proposed. This model labelled as hybrid look-up tables model is based on the combination of a memoryless look-up table sub-model and a nested look-up tables one. It is demonstrated that the proposed model circumvents the computational complexity associated with the parameters identification in analytically defined behavioral models. Moreover, the proposed model reduces the size of the standalone nested look-up tables model by approximately 80% while maintaining its accuracy. Furthermore, a novel slew-rate based trimming and indexing technique to reduce the nested look-up tables model size is developed and corroborated experimentally. Additionally, the two-box structure of the hybrid look-up tables model makes it suitable for bandwidth scalability. Experimental validation using LTE-advanced test signals with up to 120MHz bandwidth demonstrates the ability of the proposed hybrid look-up tables model to be bandwidth scalable with less than 0.5dB degradation in the normalized mean-squared error.